Bioactivity effects of extracellular matrix proteins on apical papilla cells - Leite, Maria Luísa [UNESP]; Soares, Diana Gabriela; Anovazzi, Giovana [UNESP]; Mon, Filipe Koon Wu [UNESP]; Bordini, Ester Alves Ferreira [UNESP]; Hebling, Josimeri [UNESP]; DE SOUZA COSTA, Carlos Alberto [UNESP] (FapUNIFESP (SciELO), 2021)
Potent signaling agents stimulate and guide pulp tissue regeneration, especially in endodontic treatment of teeth with incomplete root formation. Objective: This study evaluated the bioactive properties of low concentrations of extracellular matrix proteins on human apical papilla cells (hAPCs). Methodology: Different concentrations (1, 5, and 10 µg/mL) of fibronectin (FN), laminin (LM), and type I collagen (COL) were applied to the bottom of non-treated wells of sterilized 96-well plates. Non-treated and pre-treated wells were used as negative (NC) and positive (PC) controls. After seeding the hAPCs (5×103 cells/well) on the different substrates, we assessed the following parameters: adhesion, proliferation, spreading, total collagen/type I collagen synthesis and gene expression (ITGA5, ITGAV, COL1A1, COL3A1) (ANOVA/Tukey; α=0.05). Results: We observed greater attachment potential for cells on the FN substrate, with the effect depending on concentration. Concentrations of 5 and 10 µg/mL of FN yielded the highest cell proliferation, spreading and collagen synthesis values with 10 µg/mL concentration increasing the ITGA5, ITGAV, and COL1A1 expression compared with PC. LM (5 and 10 µg/mL) showed higher bioactivity values than NC, but those were lower than PC, and COL showed no bioactivity at all. Conclusion: We conclude that FN at 10 µg/mL concentration exerted the most intense bioactive effects on hAPCs.
Keywords: Collagen; Dental pulp.Fibronectin.Laminin; Guided tissue regeneration